2016
DOI: 10.1016/j.ssci.2015.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Proactive Listening to a Training Commentary improves hazard prediction

Abstract: The aim of this work was to explore the effect of Proactive Listening to a Training Commentary, using the recently developed version of the Spanish Hazard Perception test. Firstly, 16 videos were used in the pre-test session in its short version, cut to black just before the hazard appearance. The What Happens Next Assessment (at the pre-test stage) generates expectations about the outcome of the traffic situation. Then, the training (8 minutes in length) uses the complete version of the same 16 videos, reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…Additionally, research has shown hazard perception training to be effective in improving the hazard perception skills of drivers (e.g. Castro et al, 2016;Horswill, 2016;Horswill, Garth, Hill, & Watson, 2017;Vlakveld, 2014;Wetton, Hill, & Horswill, 2013). Therefore the fact that the study indicates that this training is also effective for minority groups such as those with ADHD is an important finding.…”
Section: Discussionmentioning
confidence: 86%
“…Additionally, research has shown hazard perception training to be effective in improving the hazard perception skills of drivers (e.g. Castro et al, 2016;Horswill, 2016;Horswill, Garth, Hill, & Watson, 2017;Vlakveld, 2014;Wetton, Hill, & Horswill, 2013). Therefore the fact that the study indicates that this training is also effective for minority groups such as those with ADHD is an important finding.…”
Section: Discussionmentioning
confidence: 86%
“…A number of studies have demonstrated the ability of the hazard prediction test to successfully discriminate between safer, experienced drivers, and less-safe, inexperienced drivers (Jackson et al, 2009;Crundall 2016;Castro et al, 2014, Ventsislavova et al, 2016, Gugliotta et al, 2017Lim et al, 2014). Several of these studies have also developed this occlusion-based methodology through a number of targeted experiments focusing on design elements.…”
Section: The Hazard Prediction Testmentioning
confidence: 99%
“…These initial studies suggest that the hazard prediction test can provide a robust and simpler alternative to the more traditional hazard perception test. However, one of the problems with the version of the test used by many researchers (Castro et al, 2014(Castro et al, , 2016Crundall 2016;Jackson et al, 2009) is that participants give free-response answers which must be hand coded. This introduces the potential for rater error, and renders the test impractical for use on a wide scale.…”
Section: The Hazard Prediction Testmentioning
confidence: 99%
“…Video-based commentary driver training is economical and easily accessible to drivers looking to improve their hazard perception skills; making it a desirable training method, providing it is effective. Indeed, apparent benefits have been observed in some studies with exposure to commentary videos of only eight minutes in length (Castro et al, 2016).…”
Section: Introduction Commentary Driving Involves Producing a Continumentioning
confidence: 99%
“…Benefits have been observed when drivers are trained via exposure to commentary, without ever producing a commentary of their own (Castro et al, 2016, McKenna et al, 2006Wetton et al, 2013). However, improvements in hazard perception have also been observed when trainees produced their own commentary, without ever being specifically trained in how to produce a commentary (Isler et al, 2009).…”
Section: Introduction Commentary Driving Involves Producing a Continumentioning
confidence: 99%